Hubungan Stres Kerja dengan Kualitas Tidur Perawat di Ruang Intensive Care Unit (ICU) RSUD Ulin Banjarmasin - Alya Farrah Izzati; Rida Millati; Yustan Azidin (Jurnal Kesehatan Amanah, 2026)
Work stress is a condition often experienced by nurses, especially those working in the Intensive Care Unit (ICU) due to the high demands of the job and the responsibility of caring for critically ill patients. Work stress that is not managed properly can have an impact on nurses' health, one of which is sleep quality. Poor sleep quality can reduce concentration and performance and increase work fatigue. This study aims to determine the relationship between work stress and sleep quality among nurses in the ICU of Ulin Regional General Hospital in Banjarmasin. This study uses a quantitative method with a cross-sectional design. The research sample consists of ICU nurses selected using total sampling technique. The research instruments used are the Expanded Nursing Stress Scale (ENSS) to measure work stress and the Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality. Data analysis was performed using statistical tests to determine the relationship between the two variables. The results showed that most nurses experienced moderate work stress. In addition, many nurses still had five to six hours of sleep per night and experienced sleep disturbances. The analysis results showed a significant relationship between work stress and sleep quality among ICU nurses.